ANSWER
x y
0 -2
1 -8/5
-2 -14/5
2 -6/5
Step-by-step explanation
We can solve the equation for y. First add 5y to both sides of the equation:
![\begin{gathered} 2x-5y+5y=10+5y \\ 2x=10+5y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ju81n1sbwfo3ch4vcc36r4wem7p2zxdxu0.png)
Then subtract 10 from both sides:
![\begin{gathered} 2x-10=10-10+5y \\ 2x-10=5y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qpdzdfobbj084b978dkba9skpxcz0qhyuv.png)
And divide both sides by 5:
![(2)/(5)x-2=y](https://img.qammunity.org/2023/formulas/mathematics/college/rzqakgugcanynq4jrcggr65hgfl53q8g5y.png)
And we can flip the equation so we read the y first:
![y=(2)/(5)x-2](https://img.qammunity.org/2023/formulas/mathematics/college/h5jg352ykcebx95jxvgq1ixkx11u6883js.png)
Now, to complete the table we have to replace x by each of its values in the equation above and solve to find the y-value:
![y=(2)/(5)0-2=0-2=-2](https://img.qammunity.org/2023/formulas/mathematics/college/uvt0l5j9yokywhhyx7j3ahked3hs9t3tzc.png)
![y=(2)/(5)\cdot1-2=(2)/(5)-2=-(8)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/3ybi3hi5e3s1brjdxq32ojzrprwxpdkium.png)
![y=(2)/(5)\cdot(-2)-2=-(4)/(5)-2=-(14)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/enf4xidsw9u1q8hfou0oaprkbe09g1762s.png)
![y=(2)/(5)\cdot2-2=(4)/(5)-2=-(6)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/t8u64bwkw49klejb5ciaak2iztphbsdx94.png)